Take the 2-minute tour ×
Mathematics Stack Exchange is a question and answer site for people studying math at any level and professionals in related fields. It's 100% free, no registration required.

could you please help me with following partial fractions ?

1) $$ \frac{1}{x(x^2+1)} $$

2) $$ \frac{1}{1+x^3} $$

3) $$ \frac{x}{x^3-1} $$

Thank you for very much for your time

share|improve this question
1  
This sounds like a homework problem. What have you already done? –  Jebruho Nov 28 '12 at 16:28
    
Yes it is homework, i have already done 9 previous partial fractions but in case of these three i just dont know how to decompose. –  Radoslav Ani Smolík Nov 28 '12 at 16:32

2 Answers 2

(1) For the first one the denominator is $x \cdot (x - i) \cdot (x + i)$ so we want to find numbers $A,B,C$ such that $$\frac{1}{x(x^2+1)} = \frac{A}{x}+ \frac{B}{x-i} + \frac{C}{x+i}.$$

Multiply both sides by $x(x^2+1)$ to get $$1 = (A + B + C)x^2 + i(B - C)x + A = 1$$ reading off from this we find $A=1$, $B=C$ and $1+2B=0$ so $B = -\frac{1}{2}$.

We thus have $$\frac{1}{x(x^2+1)} = \frac{1}{x} - \frac{1}{2(x-i)} + \frac{1}{2(x+i)}$$


(3) The denominator is $(x-1)(x^2+x+1)$ so we want to find numbers $A,B,C$ such that $$\frac{x}{x^3-1} = \frac{A}{x-1} + \frac{Bx + C}{x^2+x+1}$$ multiplying both sides by $x^3-1$ gives $$x = (A + B)x^2 + (A - B + C)x + (A - C)$$ thus $A=C$, $A=-B$ and $3A=1$ so we have $$\frac{x}{x^3-1} = \frac{1}{3(x-1)} + \frac{1-x}{3(x^2+x+1)}.$$

share|improve this answer

The first one is standard: $x^2+1$ is an irreducible quadratic (over the reals), so you set it up as $$\frac1{x(x^2+1)}=\frac{A}x+\frac{Bx+C}{x^2+1}\;.$$ As a quick check, note that you have three unknown coefficients, exactly as you should for a denominator of degree $3$. Recombining the righthand side over its lowest common denominator, we get

$$\frac1{x(x^2+1)}=\frac{A}x+\frac{Bx+C}{x^2+1}=\frac{A(x^2+1)+(Bx+C)x}{x(x^2+1)}$$

and therefore $A(x^2+1)+(Bx+C)x=1$. Multiply out and equate coefficients of like powers of $x$: $(A+B)x^2+Cx+A=1$, so

$$\left\{\begin{align*} A&=1&&\text{from the constant term}\\ C&=0&&\text{from the }x\text{ term}\\ A+B&=0&&\text{from the }x^2\text{ term}\;. \end{align*}\right.$$

Clearly $B=-1$, and the partial fraction decomposition is therefore

$$\frac1{x(x^2+1)}=\frac1x-\frac{x}{x^2+1}\;.$$

Each of the other two requires you to use a factorization identity; the identities in question are $$a^3+b^3=(a+b)(a^2-ab+b^2)$$ and $$a^3-b^3=(a-b)(a^2+ab+b^2)\;,$$ both of which are well worth memorizing. Then

$$\frac1{1+x^3}=\frac1{(1+x)(1-x+x^2)}=\frac{A}{1+x}+\frac{Bx+C}{1-x+x^2}$$

and

$$\frac{x}{x^3-1}=\frac{x}{(x-1)(x^2+x+1)}=\frac{A}{x-1}+\frac{Bx+C}{x^2+x+1}\;,$$

since the quadratics $x^2-x+1$ and $x^2+x+1$ are both irreducible, and you proceed as in the first problem.

share|improve this answer
    
Thank you very much. –  Radoslav Ani Smolík Nov 29 '12 at 14:53
    
@Radoslav: You’re welcome. –  Brian M. Scott Nov 29 '12 at 18:33

Your Answer

 
discard

By posting your answer, you agree to the privacy policy and terms of service.

Not the answer you're looking for? Browse other questions tagged or ask your own question.